Can the Resource Nexus guide improvements in urban planetary health? Insights from a literature review - Rayyan Sulieman; Martina Artmann; Daniel Karthe; Martin Behnisch (Resources, Environment and Sustainability)
Since 2007, cities have accommodated more than half of the global population. Their growth has led to significant environmental modifications and at least some degradation of the natural environment, with significant consumption of imported resources, waste generation and pollutant emissions. This on the one hand leads to a special importance of cities for planetary health, and on the other hand underlines the necessity of integrated approaches in environmental resources management for improving urban planetary health. However, the role of integrative approaches, such as the Resource Nexus, in urban planetary health remains insufficiently explored. This study addresses this gap by conducting a semi-systematic literature review, following the PRISMA guidelines to select and document the current state of knowledge on urban planetary health and the role of the Resource Nexus approach for sustainability transformations in this context. Based on 57 papers, a qualitative text analysis was conducted through the lens of the Resource Nexus framework. It was found that all key environmental resources are covered regarding their role for urban planetary health, with climate, food, biota, land, and water identified as the most critical elements for enhancing planetary health. Moreover, the analysed literature shows that despite the many challenges, urban areas offer a multitude of opportunities for societal, political, and economic interventions that can benefit environmental and human health. Maximizing synergies and minimizing trade-offs requires addressing both challenges and opportunities. This often involves making multiple changes at both the urban societal and governance levels. These changes create a systemic shift, moving away from prioritizing economic prosperity and towards a focus on planetary health.